Mapping Artificial Intelligence for Generation Z: A Systematic Literature Review of the Implications and Future Research Directions - Sunarto, M. J. Dewiyani; Wardhanie, Ayouvi Poerna; Lemantara, Julianto; Kisworo, Angen Yudho (CV Sinergi Ilmu dan Publikasi, 2026)
As artificial intelligence continues to evolve rapidly, it presents valuable opportunities for enhancing education for educators and Gen-Z learners. However, fully harnessing its potential to improve learning outcomes remains a complex challenge. This study aims to provide a critical mapping of research trends and gaps in the application of artificial intelligence for Generation Z in higher education by examining AI’s impacts, contributions, and future research directions. The research analyzes 40 Scopus-indexed articles from the past ten years using a systematic literature review based on the PRISMA framework. The focus is on identifying, evaluating, and interpreting existing studies on AI's integration in Gen Z education, guided by specific research questions. AI influences every stage of education and streamlines tasks like attendance tracking, financial management, and student counseling. It also has the potential to foster critical thinking, creativity, and communication skills. However, concerns arise around academic integrity when students misuse AI tools to bypass genuine learning. The study's key contribution is its exploration of how AI can support personalized learning through four core dimensions: learning, teaching, assessment, and administration. Such dimension-specific investigations will strengthen the practical applicability of AI in higher education and advance evidence-based educational innovation for Generation Z.